Spatial distribution of the Mexican fruit fly complex (Anastrepha spp.) (Diptera: Tephritidae) in Michoacán, México. (2021)
Globally, fruit production is one of the main sources of income since it generates large economic spills for producers, however, it is affected by various pests. In Mexico, the Mexican fruit fly is one of the main pests that cause considerable economic damage. Fruit oviposited by this pest usually is no longer accepted in the market causing large economic losses to the producers. The alternative controls against this pest have been ineffective due, among other causes, to the fact that their spatial distribution within plum, orange, sapote, guava and mango orchards is unknown. Therefore, this work aimed to determine the spatial distribution of the Mexican fruit fly populations in these orchards, through the application of spatial statistics techniques and the generation of maps through "kriging". The results showed that populations of this fruit pest have an aggregate distribution, which was corroborated by density maps. Infestations were distributed in different areas of the orchards, which would be useful to direct control measures on specific areas of infestation.